Robust spin-on-glass poly(methyl)silsesquioxane-based low-k materials derived from a cyclic siloxane precursor - Lee, Albert S.; Oh, Sung Yeoun; Choi, Seung-Sock; Lee, He Seung; Hwang, Seung Sang; Baek, Kyung-Youl (ROYAL SOC CHEMISTRY, 2015)
A series of organic-inorganic hybrid spin-on-glass polymethylsilsesquioxanes were synthesized utilizing a cyclic siloxane precursor, 1,3,5,7-tetramethyl-1,3,5,7-tetrahydroxyl cyclosiloxane (MT4-OH), copolymerized with methyltriethoxysilane (MTES) at various comonomer ratios. By selectively introducing this 2-D cyclic crosslinker, we were able to obtain spin-on-glass hybrimers with low dielectric constant (2.5-2.7), high nanoindentation modulus (5-10.5 GPa), with high thermal stability (> 700 degrees C) without the use of porogens or additives. The use of the cyclic monomer MT4-OH greatly increased the mechanical properties, which allowed for impeccable reliability of a variety of patterns obtained through etching and chemical mechanical planarization processes, while maintaining optimal gap-filling properties. Due to the superior dielectric, mechanical, and integrated processing of these materials, these hybrids derived from MT4-OH may be utilized as next generation spin-on-glass low-dielectric constant materials.